An overview on basics of organic and dye sensitized solar cells, their mechanism and recent improvements. (October 2017) - Kumavat, Priyanka P.; Sonar, Prashant; Dalal, Dipak S.
Abstract: Organic and dye sensitized solar cell devices have attracted a significant attention during last few years in scientific community due to their advantages such as low cost, easy processibility, large scale manufacturing and efficient conversion of solar energy into electrical energy. The main aim of this review is to provide torchlight for organic chemist willing to start exploration in the field of solar cell as it includes an overview of organic and dye sensitized solar cells. This review covers detailed history for development of solar cell, some basic terminologies used in organic and dye sensitized solar cells. The review article gives attention toward synthetic utility of organic molecules for different types of solar cell such as single layer, double layer and bulk heterojunction solar cells, their mechanisms and type of materials which are generally used for solar cell device fabrication. The review specially gives focus on the up to date information about improvements in Organic Solar Cells (OSCs) and Dye Sensitized Solar Cells (DSSCs) which will be a handy tool for young budding researchers to explore the molecular engineering opportunities in terms of designing and synthesizing more efficient exotic materials for solar cell. Graphical abstract: fx1